2021
DOI: 10.1186/s13613-021-00877-7
|View full text |Cite
|
Sign up to set email alerts
|

Individualization of PEEP and tidal volume in ARDS patients with electrical impedance tomography: a pilot feasibility study

Abstract: Background In mechanically ventilated patients with acute respiratory distress syndrome (ARDS), electrical impedance tomography (EIT) provides information on alveolar cycling and overdistension as well as assessment of recruitability at the bedside. We developed a protocol for individualization of positive end-expiratory pressure (PEEP) and tidal volume (VT) utilizing EIT-derived information on recruitability, overdistension and alveolar cycling. The aim of this study was to assess whether the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Previous research [16] showed that slow inflation with a constant gas flow is obligatory for sufficient RVDI calculation and the assessment of tidal recruitment. In a recent study in patients with ARDS, Becher et al [30] used EIT to individually adjust PEEP and V T . Using a modified algorithm for RVDI measurements during a slow inflation of 12 mL/kg BW, Becher et al demonstrated that time disparities in regional ventilation were reduced with EIT-based PEEP settings in comparison with clinical PEEP settings.…”
Section: Individualized Peep Titration Based On Global and Regional Information About Lung Mechanicsmentioning
confidence: 99%
“…Previous research [16] showed that slow inflation with a constant gas flow is obligatory for sufficient RVDI calculation and the assessment of tidal recruitment. In a recent study in patients with ARDS, Becher et al [30] used EIT to individually adjust PEEP and V T . Using a modified algorithm for RVDI measurements during a slow inflation of 12 mL/kg BW, Becher et al demonstrated that time disparities in regional ventilation were reduced with EIT-based PEEP settings in comparison with clinical PEEP settings.…”
Section: Individualized Peep Titration Based On Global and Regional Information About Lung Mechanicsmentioning
confidence: 99%
“…Possible directions of development of this area were shown. Just as in paper [4], the aspects of personalization of the parameters of the EIT examination itself, such as the parameters of injected current, the type of used electrodes, the place of their imposition, remained unresolved. In these works, the importance of the influence of these factors on the final result of the examination is evidently underestimated.…”
Section: Designing a Bench For Testing Medically And Technically An Information And Measuring System For Multi-frequency Electrical Impedmentioning
confidence: 99%
“…Currently, the problem of long-term monitoring of the functional state of human lungs is one of the most important areas of respiratory support for patients. Among them, the possibility of long-term bedside monitoring of the breathing process in the pre-and postoperative period, including patients connected to devices of artificial ventilation of lungs (AVL) [4][5][6], is of great clinical importance.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…EIT generates cross-sectional images of the impedance distribution within the thorax and measures continuously regional lung volume changes at the bedside ( Hinz et al, 2003 ; Kotani et al, 2016 ; Aguirre-Bermeo et al, 2018 ; Holanda et al, 2018 ). EIT is widely used in lung ventilation assessment in hypoxemia patients, including the PEEP titration (Dalla Corte et al, 2020 ; He et al, 2021 ; He et al, 2020 ; Yun et al, 2016 ; Becher et al, 2021 ; Gibot et al, 2021 ; Muders et al, 2021 ; Scaramuzzo et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%